2015
DOI: 10.1108/mi-12-2013-0080
|View full text |Cite
|
Sign up to set email alerts
|

Electric, magnetic and high frequency properties of screen printed ferrite-ferroelectric composite thick films on alumina substrate

Abstract: Purpose – The purpose of this article is to study the effect of ferrite content on electric, magnetic and microwave properties of screen-printed y(Ni0.4Co0.2Cd0.4Fe2O4) + (1 − y)Pb(Zr0.52Ti0.48)O3 (y = 0.0, 0.15, 0.30, 0.45, 1.0) thick films on alumina. Design/methodology/approach – Thick films of ferrite–ferroelectric composite on alumina substrate have been delineated using screen printing technique. The structural analysis was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…For the convenience of applying a protective material on the surface, ready-made paints of two types were chosen as a matrix. The first is the acrylic water-dispersion paint VD˗AK˗22W (Belarus) (ρ=1.03 g/cm 3 ), the second is the geopolymer paint MK 3/18˗9.20 (Ukraine) (ρ=1.15 g/cm 3 ).…”
Section: Materials and Methods To Study Liquid Composite Materials For Shielding Electromagnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the convenience of applying a protective material on the surface, ready-made paints of two types were chosen as a matrix. The first is the acrylic water-dispersion paint VD˗AK˗22W (Belarus) (ρ=1.03 g/cm 3 ), the second is the geopolymer paint MK 3/18˗9.20 (Ukraine) (ρ=1.15 g/cm 3 ).…”
Section: Materials and Methods To Study Liquid Composite Materials For Shielding Electromagnetic Fieldsmentioning
confidence: 99%
“…This is due to an increase in the number and density of the location of electrical and electronic equipment in production facilities, an increase in the load on power structures. Study [3] identified the protective properties of a material made of polymer matrix and a metal filler made of ferrite of micro size. Recently, a significant part of studies addresses the development of compositions based on metal and metal-containing nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…It also refers to materials with microwires [3]. These shortcomings are not inherent in the materials with a uniform distribution of the shielding substance in the body of a material (matrix) [4]. However, ferrite particles in the matrix are of large size, which makes the material thickness (1 mm or larger) unacceptable for the manufacture of protective clothing.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The use of the ethyl alcohol-based fluid, with the subsequent neutralization of oleic acid by an alkaline solution, turned out to be impractical because of the washout or chemical destruction of the nano-particles by alkali, which was confirmed experimentally. 4. In order to determine the possibility of manufacturing special clothing from the designed material aimed to protect against electrical and magnetic fields, we simulated the magnetic field distribution in the human body using a finite element method and the Comsol software.…”
Section: B0 B0 B0mentioning
confidence: 99%
“…That is why at low (13-15 % by weight) content of metal, reflection coefficients amount to 0.3-0.6, which is unacceptable under production conditions with a large density of arrangement of technological equipment. These deficiencies are partially eliminated in the elastic electromagnetic screen based on ferrite-aluminum [8]. An analysis revealed that it is very difficult to manufacture and is very expensive.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%